MILITANSI BERAGAMA DI KOTA KEDIRI - yani, sri mul (KOMUNIKASIA: Journal of Islamic Communication and Broadcasting, 2022)
Religion that is global and dramatic in people's lives creates pluralism. Religious militancy in the public sphere is required to be mutually transparent and inclusive. Multiculturalism has given rise to religious movements with various applied sciences. The emergence of religious groups in the community in an area sometimes creates a variant of perception. These dynamics follow the rhythm of the frictions of the reality of life. This striking symbol and different characteristics have created a flurry of perception from groups who are not as Kufu. In the city of Kediri, there is a place of worship that is thought to be the center of a different and exclusive group. Positive and negative stigma emerges from several public perceptions of this phenomenon. The mixed fanfare was motivated by several factors. For that we need understanding from each individual or group. Because every individual has a variety of differences in ideological views. This can be influenced by religious understanding, educational background, and experience of each person. Thus, extensive knowledge is needed to address and assess in order to avoid misunderstandings and social inequality. Some of the areas studied by the researcher are about the symbols and various essential motives hidden behind the presence of militant groups. Therefore, the researcher dissects this sensitive phenomenon using perception theory from the perspective of Roland Barthes' semiotica.